Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: • The impact of digitizing healthcare services on hospital performance in the Kingdom of Saudi Arabia Dr. Samiyah Rafan Althaqafy, Dr. Mohammad Abdullah Barnawy ,Mr. Faris Omar Batawi • The Role of Explainable Artificial Intelligence (XAI) in Supporting Knowledge Management (KM) and Its Processes: An Analytical Study Ms. Mashael Abdulrahman Al-Hazmi, Ms. Enas Mohammed Al-Najjar, Ms. Wafa Mohna Al-Shaikh • The Impact of Humble Leadership on Enhancing Organizational Commitment "A Field Study of Employees in the Emirate of Jazan Region" Mr. Laghabi Mohammed Yahya, Prof. Alariki, Baseim Qaid • The Impact of Flexible Work Environment on Employee Productivity: A Survey Study at Zain Iraq Telecommunications Company Lecturer Asrar Abdulzahra Ali • The Impact of War Conditions on Multidimensional Poverty and Development in Northwestern Syria: A Field Study of Idlib and Aleppo Governorates in 2024 Mr. Ayaz Shukri Taher, Prof. Samir Al-Chikh Ali • The Impact of Using the Balanced Scorecard in Enhancing Organizational Agility: An Applied Study on Technical Colleges in the Asir Region Ms. Raghad Ali Mohammed ,Prof. Mohsen Al-Dabbabi • The Size and Contribution of the Informal Economy in Jordan during the Period 2019-2023 Dr. Jihad Ahmad Abu Al-Sondos • Forensic Accounting before the Libyan Judiciary as a Mechanism to Reduce Financial Corruption: A Field Analytical Study Ms. Fathya Gebril Shaitir ,Prof. Jazia Gebril Shaitir